1997
DOI: 10.1111/j.1749-6632.1997.tb52125.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Hypothalamic‐Pituitary‐Ovarian Axis

Abstract: The onset of puberty is a centrally driven process, the detailed mechanisms of which are not known. It is translated into an increased activity of the hypothalamic GnRH pulse generator. This in turn is seen as increased pituitary pulsatile secretion of LH and FSH. LH pulses are observed even in midchildhood, particularly after the onset of sleep. Onset of puberty is associated with a greater increase in LH pulse amplitude than frequency and a much greater increase in LH and FSH. A progressive increase in dayti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…For example, leptin levels are predictive of early menarche, 38 and levels are higher among black girls than white girls. 39 Racial differences may also exist in other characteristics that have been suggested to influence pubertal development, such as the secretion of hormones by the hypothalamus, anterior pituitary, and ovary 40 ; social stress 41 ; organic pollutants 42 ; and hormone-containing hair products. 43 The most important limitation of the current study may be our use of self-reported menarcheal age.…”
Section: Discussionmentioning
confidence: 99%
“…For example, leptin levels are predictive of early menarche, 38 and levels are higher among black girls than white girls. 39 Racial differences may also exist in other characteristics that have been suggested to influence pubertal development, such as the secretion of hormones by the hypothalamus, anterior pituitary, and ovary 40 ; social stress 41 ; organic pollutants 42 ; and hormone-containing hair products. 43 The most important limitation of the current study may be our use of self-reported menarcheal age.…”
Section: Discussionmentioning
confidence: 99%
“…[196]). Yet, initiation of puberty does not rely on alterations in sensitivity to gonadal steroid feedback; there are species differences in these feedback systems [428], and pubertal activation of pulsatile GnRH release is evident even in patients with gonadal agenesis [21].…”
Section: Attenuation Of Inhibitory Tonementioning
confidence: 99%
“…This is an important question for several reasons. First, the pubertal period is associated with dramatic changes in circulating hormones, comparable to, if not greater than, (Apter, 1997) changes occurring during reproductive aging (Hammond, 1996). Second, hormone-associated changes in brain plasticity such as neurite outgrowth, spinogenesis, synaptogenesis, and expression of neurotransmitter receptors are observed during puberty in neuroendocrine brain regions (Anderson, 1982;Cottrell et al, 2006;Gore et al, 1996;Matsumoto & Arai, 1976;Reier et al, 1977); however such analyses have not been systematically studied in hippocampal brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Pubertal developmental in female mammals is characterized by dramatic increases in circulating estradiol concentrations (Apter, 1997;see Table 1). This hormone acts on targets throughout the body and the brain, where estrogen receptors are widely expressed (Chakraborty & Gore, 2004;Mitra et al, 2003).…”
Section: Hippocampal Plasticity and Pubertymentioning
confidence: 99%